Osmostress-induced changes in yeast gene expression - Varela, J. (2014)
When Saccharomyces cerevisiae cells are exposed to high concentrations of NaCI, they show reduced viability, methionine uptake and protein biosynthesis. Cells can acquire tolerance against a severe salt shock (up to 1.4 M NaCI) by a previous treatment with 0.7 M NaCI, but not by a previous heat shock. Two-dimensional analysis of [3H]-leucine-labelled proteins from salt-shocked cells (0.7 M NaCt) revealed the elevated rate of synthesis of nine proteins, among which were the heat-shock proteins hsp12 and hsp26. Northern analysis using gene-specific probes confirmed the identity of the latter proteins and, in addition, demonstrated the induction of glycerol-3-phos-phate dehydrogenase gene expression. The synthesis of the same set of proteins is induced or enhanced upon exposure of cells to 0.8 M sucrose, although not as dramatically as in an iso-osmolar NaCI concentration (0.7 M).